2021
DOI: 10.1002/pssr.202100039
|View full text |Cite
|
Sign up to set email alerts
|

Dirac Semimetal Protected by Nonsymmorphic Mirror Symmetries in TPH‐Graphene

Abstract: Dirac cones in 2D carbon allotropes are generally protected by symmorphic symmetry operations. Herein, it is proposed that TPH-graphene has Dirac cones protected by nonsymmorphic mirror symmetries. This monolayer is composed of tetragonal, pentagonal, and heptagonal carbon rings and exhibits not only good mechanical and dynamic stability but also high energetic stability. The structure has anisotropic mechanical properties, and its Young's modulus is close to that of graphene, up to 291 N m À1 . The Dirac poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…We can find that there are two Dirac cones on high-symmetry line Γ-Y and the edge states clearly can be seen. The edge states are similar to that of other 2D Dirac semimetallic materials when SOC is not considered, such as 1T'-WTe 2 , [10] TPH-graphene, [63] ZrOH, [64] and borophene. [65] The 3D energy bands show that Dirac cone only exists on Γ-Y and there is no Dirac cone along the path of Γ-X.…”
Section: It Is Also Indicated That the Number Of Dirac Points Issupporting
confidence: 59%
“…We can find that there are two Dirac cones on high-symmetry line Γ-Y and the edge states clearly can be seen. The edge states are similar to that of other 2D Dirac semimetallic materials when SOC is not considered, such as 1T'-WTe 2 , [10] TPH-graphene, [63] ZrOH, [64] and borophene. [65] The 3D energy bands show that Dirac cone only exists on Γ-Y and there is no Dirac cone along the path of Γ-X.…”
Section: It Is Also Indicated That the Number Of Dirac Points Issupporting
confidence: 59%
“…It can be shown that, despite having greater energy than graphene (À9.225 eV per atom). It is substantially lower than many other 2D carbon allotropes proposed in theory, [24][25][26][27][28][29][30] which illustrates that the experimental synthesis of this structure has a great possibility.…”
Section: Structure and Stabilitymentioning
confidence: 65%
“…The stability of the TPH‐graphene and some of the graphene allotropes is briefly discussed in the recent literature. [ 40 ] The stability is in the order of graphene [−9.22 eV/atom], PAI‐graphene (5–6–7 carbon polygons) [−9.08 eV/atom], TPH‐graphene [−8.83 eV/atom], cp‐graphyne (5‐acetylenic‐type linker) [−8.534 eV/atom], and γ‐graphdiyne [−8.462 eV/atom]. It indicates that the TPH‐graphene shows reasonable stability.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of the TPH-graphene and some of the graphene allotropes is briefly discussed in the recent literature. [40] The stability is in the order of graphene [À9.…”
Section: Structurementioning
confidence: 99%